Ultraviolet In Situ Polymerized Binders with Polysulfide‐Trapping Properties for Long‐Cycle‐Life Lithium–Sulfur Batteries. Issue 19 (22nd June 2022) - Chen, Zhuzuan; Peng, Yuehai; Yang, Zhuohong; Yang, Yu
Abstract: Lithium–sulfur batteries (LSBs) represent a promising energy storage system due to the high theoretical energy density of the cathode; however, the high temperature and long‐time drying required for electrode production result in high energy consumption and low efficiency. Ultraviolet (UV)‐curing technology is an effective strategy to solve the abovementioned problems. However, carbon black and other conductive agents used in the production of the battery industry show strong absorption of UV light; thus, a single photoinitiator cannot absorb enough light intensity to realize initiation, limiting its application in the battery industry. In this work, the concept of full‐band absorption is introduced into the manufacturing process of the LSB cathode to solve the abovementioned problems. The full‐band absorption of photoinitiators in the UV band is successfully realized by combining the photoinitiators 2‐benzyl‐2‐dimethylamino‐1‐(4‐morpholinylphenyl)‐1‐butanone, 2‐isopropyl thioxanthone, and bis (2, 4, 6‐trimethyl benzoyl)‐phenoxyphosphine. An ultraviolet in situ polymerized polyurethane acrylate (PUA) binder is successfully prepared by the combination of photoinitiators. PUA is used as the binder of LSBs and exhibits an excellent long‐cycle performance of 1500 cycles with a low decay rate of 0.04% per cycle at 0.5 C. Thus, UV‐curing technology provides a new prospect and possibility of industrialization for battery manufacturing. Abstract : In this work, it is demonstrated that sulfur cathodes can be successfully fabricated by in situ ultraviolet curing method. The results show that this strategy shifts the electrode fabrication process from high temperature and long‐time drying, to fast and low‐temperature drying, which can effectively save energy and improve efficiency.